2011
DOI: 10.1021/nn202638t
|View full text |Cite
|
Sign up to set email alerts
|

General Pathway toward Crystalline-Core Micelles with Tunable Morphology and Corona Segregation

Abstract: We present a general mechanism for the solution self-assembly of crystalline-core micelles (CCMs) from triblock copolymers bearing a semicrystalline polyethylene (PE) middle block. This approach enables the production of nanoparticles with tunable dimensions and surface structures. Depending on the quality of the solvent used for PE, either spherical or worm-like CCMs can be generated in an easy and highly selective fashion from the same triblock copolymers via crystallization-induced self-assembly upon coolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
264
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(271 citation statements)
references
References 61 publications
(130 reference statements)
3
264
1
2
Order By: Relevance
“…Seeded-growth of crystallizable BCPs from 1D cylindrical seeds prepared by sonication of long, polydisperse cylinders with a crystalline core provides a recently established route to low dispersity cylindrical micelles of controlled length [18][19][20] and also complex architectures such as block comicelles, [21][22][23] branched cylindrical micelles, 24 and multi-armed micelles. 25 The key to this approach is that the core termini of the seeds remain active to the addition of further BCP unimer, leading to a process that is analogous to a living covalent polymerization of molecular monomers.…”
Section: Seeded Growth Of Pfs Homopolymers With Charged End-groups Usmentioning
confidence: 99%
“…Seeded-growth of crystallizable BCPs from 1D cylindrical seeds prepared by sonication of long, polydisperse cylinders with a crystalline core provides a recently established route to low dispersity cylindrical micelles of controlled length [18][19][20] and also complex architectures such as block comicelles, [21][22][23] branched cylindrical micelles, 24 and multi-armed micelles. 25 The key to this approach is that the core termini of the seeds remain active to the addition of further BCP unimer, leading to a process that is analogous to a living covalent polymerization of molecular monomers.…”
Section: Seeded Growth Of Pfs Homopolymers With Charged End-groups Usmentioning
confidence: 99%
“…Confinement of polymer systems can be generally classified into three categories according to their confined environments, and they are one, two and three dimensions, respectively. Confined crystallization of polymers has been found in a variety of systems, such as polymer ultrathin films [1][2][3][4][5], polymer blends [6][7][8][9][10], block copolymers [11][12][13][14], polymer droplets [15][16][17], self-assembled polymer nanostructures [18][19][20][21][22], polymers segregated inside nanoporous templates [23][24][25][26][27][28][29] and polymer nanocomposites [30][31][32][33]. In the past few years, the crystallization of polymers or polymer segments confined in ultrathin films (thickness <100 nm), miscible polymer blends and block copolymers has been widely studied for various systems.…”
Section: Introductionmentioning
confidence: 99%
“…The WAXS pattern for P3C7Se 18 -b -PS 125 micelles dropcast from n BuOAc was found to be similar to that for the P3C7Se 18 [ 68 ] Crystalline P3AT fi lms are known to exhibit two different crystal structures designated type-1 and type-2. [ 68,81 ] The type-1 polymorph exhibits thicker layers and a lower degree of alkyl chain interdigitation by WAXS analysis.…”
Section: Waxs Studies Of P3c7se 18 -B -Ps 125 Diblock Copolymer Micellesmentioning
confidence: 99%
“…The solution self-assembly of amphiphilic "coil-coil" diblock copolymers, where both blocks are amorphous and behave as random coils in solution has been well studied and offers an important "bottom-up" route to nanoscale soft materials with applications such as drug delivery vehicles, nanoreactors, templates, and stimuli-responsive has been demonstrated for a wide variety of asymmetric diblock copolymers containing crystallizable core-forming segments including polyethylene, [ 8,[17][18][19] poly(ethylene oxide), [ 20 ] poly(Δ-caprolactone), [ 21,22 ] poly(Δ-caprolactoneb -L -lactide), [ 23 ] polylactide, [ 7,24 ] polyacrylonitrile, [ 25 ] poly(ferrocenyldimethylsilane) (PFS), [ 26,27 ] poly(ferrocen yldimethylgermane), [ 28 ] poly(ferrocenyldiethylsilane), [ 29 ] poly(perfl uoro-octylethylmethacrylate), [ 30 ] cyclic polypeptoids, [ 31 ] and even smectic liquid crystalline polymers. [ 32 ] In several cases, it has been demonstrated that the dimensions of micelles formed by CDSA can be controlled by a living process analogous to a living covalent polymerization.…”
Section: Introductionmentioning
confidence: 99%